PENENTUAN KONDISI OPTIMUM PRODUKSI ENZIM KERATINASE OLEH Actinobacillus spp. MENGGUNAKAN TEPUNG BULU AYAM SEBAGAI SUBSTRAT PADA FERMENTASI MEDIA CAIR - Desi Susanti; Suci Rahmi (Jurnal Teknologi Pengolahan Pertanian, 2021)
Keratinase enzyme is a monomeric enzyme, this enzyme can hydrolyze keratin protein found in chicken feathers. It is estimated that about 90% of the protein contained in chicken feathers is keratin protein, this protein is difficult to digest because of the strong disulfide cross-links and other bonds. Biological processing of chicken feather flour with enzyme treatment produced by microorganisms during the fermentation process under optimal conditions produces high quality feather flour. There are several factors that affect the activity of the keratinase enzyme, including: dose inoculum, temperature, pH, substrate concentration, enzyme deposition, and fermentation time. This study aims to obtain the best optimum conditions (pH, substrate concentration, inoculum dose and fermentation time) of Actinobacillus spp in producing keratinase enzymes using chicken feather flour as a substrate in liquid medium. The main ingredients used in this study are: chicken feather flour, NA (Nutrient Agar), Aquades and substances used for liquid media and bacteria Actinobacillus spp. The study used an experimental method with 4 treatments consisting of pH (9.0; 9.5; 10; 10.5 and pH 11), sedimentation substrate (0.5%; 1%; 1.5%; 2%; 2 ,5%), inoculum dose (1 ml, 1.5 ml, 2 ml, 2.5 ml, 3 ml) and fermentation time 1 to 7 days, each treatment was repeated 3 times. The results showed that the optimum fermentation conditions of Actinobacillus spp in producing keratinase enzyme with an optimum pH of 9, optimum substrate concentration of 1%, inoculum dose of 1.5 ml, and optimum fermentation time of 2 days. Keyword : Actinobacillus spp; chicken feather flour; keratinase enzyme activity; optimumcondition